Geoecological justification of a project of sustainable shipping on a Volga channel section in the Nizhny Novgorod region - Yu. A. Mamaev; S. V. Kozlovsky; A. A. Yastrebov (Известия высших учебных заведений: Геология и разведка, 2021)
Background. The Volga river channel with rapids limiting the navigation parameters of large-tonnage vessels between the cities of Gorodets and Nizhniy Novgorod is considered in the structure of the Unified deep-water system of waterways of the European part of the Russian Federation.Aim. To justify the need to develop design solutions providing sustainable navigation in the limiting river section under study during the entire navigation period.Materials and methods. An analysis of engineering-geological and geoecological conditions of the region, including a limiting channel section of the Volga.Results. The engineering-geological and geoecological conditions of the region were characterized. A brief description of individual project proposals, including two priority construction projects, a low-pressure hydroelectric unit and a ship canal, was provided with a comparative assessment of natural and man-made factors arising during their implementation.Conclusion. The implementation of the project for the construction of the Volgo-Don 2 canal should be an important stage in the development of the Unified deep-water system of waterways in the European part of the Russian Federation. It will replenish the Don River from the Volga in order to improve navigation conditions, land irrigation, water supply to settlements, and power generation.